Rectal Carcinoma Metastasis to Oral Cavity: A Rare Presentation - Mane-Patil, Ashwini Dhananjay; Mane, Prashant Shivaji (Annals of Pathology and Laboratory Medicine, 2020)
Colorectal cancer is 3rd most common cancer all over the world. Metastasis in colorectal cancer is common and seen in approximately 30% cases. Metastatic pattern in colorectal cancer depends upon the primary tumour site and histological subtypes. Liver is the most common site for metastasis. Oral cavity is very rare site for metastasis. Here, we report a case of 52 year old male, diagnosed with rectal adenocarcinoma with liver and lung metastases and presenting with oral ulcer. Histopathological examination of oral ulcer revealed metastatic adenocarcinoma. We are presenting it as a rare case report and reviewing similar published cases.